Respiratory Infections and Bronchiectasis 2021
DOI: 10.1183/13993003.congress-2021.pa3820
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 seropositivity in asymptomatic frontline health workers in Ibadan, Nigeria

Abstract: Global health has been thrown into turmoil by the COVID-19 pandemic, which has caused devastating morbidity and unprecedented loss of life in almost all continents of the world. It was predicted that the magnitude of the pandemic in Africa will be high because of poor health structure and intensely poor living condition, but that has not happened, surprisingly. It was hypothesized that the youthful population and a vastly primed immune system were protective, and many people may have been exposed without comin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Decreased diagnostic capacity has been reported to play a role in low reported COVID-19-related mortality. However, reduced testing would actually artificially inflate case fatality rates, since asymptomatic cases are mostly missed, whereas large-scale deaths are hard to miss [8,[13][14][15]. It is more likely that host factors may play a part in driving the different proportions of symptomatic and asymptomatic cases in West Africa relative to the rest of Africa and the world.…”
Section: Introductionmentioning
confidence: 99%
“…Decreased diagnostic capacity has been reported to play a role in low reported COVID-19-related mortality. However, reduced testing would actually artificially inflate case fatality rates, since asymptomatic cases are mostly missed, whereas large-scale deaths are hard to miss [8,[13][14][15]. It is more likely that host factors may play a part in driving the different proportions of symptomatic and asymptomatic cases in West Africa relative to the rest of Africa and the world.…”
Section: Introductionmentioning
confidence: 99%
“…However, so far, evidence has shown that the epidemiology of the COVID-19 pandemic in sub-Saharan Africa has been different from the Americas, China, and Europe [1]. Available seroprevalence data indicate that SARS-CoV-2 has circulated more widely in African populations than can be deduced from the number of reported confirmed cases, hospitalisations, and deaths [5][6][7][8]. This has led to speculations that SARS-CoV-2 could have circulated longer in sub-Saharan Africa than the first confirmed cases, but current evidence is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Blood donor serosurveys are well-used surrogates for population surveillance of infectious diseases and have been used together with healthcare worker serosurveys to estimate and monitor the extent of the SARS-CoV-2 pandemic in several countries [5][6][7][8]. Here, we report results of a national serosurvey using archived serum samples from blood transfusion donors across Malawi from January 2020 to July 2021, generated using a World Health Organization (WHO)-recommended anti-SARS-CoV-2 receptor-binding domain total antibody assay with high sensitivity and specificity, supported by SARS-CoV-2 pseudovirus neutralisation assays to explore variant specificity.…”
Section: Introductionmentioning
confidence: 99%
“…[10] Mortality surveillance involves reporting and monitoring the number of monkeypox deaths in the community, hospitals, and other sites. [11][12][13] The number of deaths is recorded daily or weekly, [6,14] hence hospital-based surveillance is another form of facility-based surveillance that takes place within the hospital. [15] Challenges of the surveillance system in Nigeria Numerous activities require expertise for effective surveillance outcomes.…”
Section: Forms Of Surveillance System For Monkeypox Virusmentioning
confidence: 99%